EFFECTIVE ENTREPRENEURIAL DEVELOPMENT CENTRES: GATEWAY TO SUSTAINABLE FINANCIAL INDEPENDENCE OF NIGERIAN TERTIARY STUDENTS AND GRADUATES (Journal of the Management Sciences, 2025)
Faced with lots of socioeconomic challenges, which range from mass unemployment to high rate of inflation, dwindling foreign direct investments, and steady depreciation of the naira ultimately culminating in widespread poverty, massive entrepreneurship through effective entrepreneurial education of the undergraduate population, tend to be the way to go, for Nigeria to surmount her overwhelming socioeconomic quagmire. Consequently, this paper sought to: Identify practical and viable entrepreneurial skills that can be acquired by Nigerian tertiary students through campus entrepreneurial development centers (EDCs); examine basic requirements and standards for the effective transfer of entrepreneurial knowledge and skills to the trainees; proffer models for trainees’ business start-up, financing, promotion and long term sustainability. Using a structured literature review approach, some past related studies were x-rayed to establish the relationship between entrepreneurship education and economic emancipation especially as it has to do with financial independence of the undergraduate and graduate population. Subsequently, viable entrepreneurial and vocational areas were identified as skills that Nigerian undergraduates can be trained in through their respective entrepreneurial development centers (EDCs) on campus. However, for achievement of effective entrepreneurial knowledge and skills transfer to trainees, adequate funding, standardization and equipping of the EDCs were identified as being paramount in addition to the fulfillment of other certain requirements. Finally, feasible and efficient models for trainees’ business start-up, financing, promotion and long term sustainability were proffered, and thus initiating a sustainable model for the financial independence of Nigerian tertiary students and graduates through practical and effective entrepreneurial education using the campus EDCs.
Keywords: Entrepreneurial development; undergraduate population; financial independence; sustainability